Penguatan Infrastruktur Digital Desa Melalui Penerapan Jaringan RT/RW-Net Dan Pelatihan Pemanfaatan Aplikasi Smart Village - Wowon Priatna; Tyastuti Sri Lestari; Rasim (Jurnal Pengabdian kepada Masyarakat UBJ, 2026)
The digital transformation of rural areas has become a national priority to improve public service efficiency and strengthen technology-based village governance. This community service program aimed to enhance the digital infrastructure of Neglasari Village, Darmaraja District, Sumedang Regency, through the implementation of an RT/RW-Net network and training on the utilization of a Smart Village application. The program involved the deployment of RT/RW-Net as the village’s digital backbone, the development of a web-based Smart Village application using the PHP Laravel framework and MySQL database, and structured training sessions for village officials, administrators, operators, and residents. The training adopted participatory and hands-on methods covering network configuration and maintenance, operation of digital administrative services such as online letter requests and complaint management, and integration of population data.The results indicate that the RT/RW-Net infrastructure operated reliably and supported the optimal performance of the Smart Village application. Training activities significantly improved the technical capacity of village officials and operators, enabling independent management of the network and application. Residents also began utilizing digital services for administrative needs, complaints, and access to population information, leading to more efficient, effective, and transparent public services. This initiative demonstrates that the integration of localized digital infrastructure and practice-oriented capacity building can serve as a sustainable and scalable model for accelerating digital transformation in rural communities. Future development should focus on expanding application features, strengthening digital literacy, and promoting data-driven village governance.